2012
DOI: 10.2174/1874306401206010059
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alkalosis in Adults with Stable Cystic Fibrosis

Abstract: Background: The frequency of metabolic alkalosis among adults with stable severe CF-lung disease is unknown.Methods: Retrospective chart review.Results: Fourteen CF and 6 COPD (controls) patients were included. FEV1 was similar between the two groups. PaO2 was significantly higher in the COPD (mean ± 2 SD is 72.0 ± 6.8 mmHg,) than in the CF group (56.1 ± 4.1 mmHg). The frequency of metabolic alkalosis in CF patients (12/14, 86%) was significantly greater (p=0.04) than in the COPD group (2/6, 33%). Mixed respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…It has been previously suggested that a concomitant metabolic alkalosis contributes to hypercapnic respiratory failure in exacerbations of adult CF and that these patients less frequently exhibit acidosis than COPD patients due to the abnormal electrolyte transport in CF patients compared to COPD, even during exacerbations [ 35 , 36 ]. This may have been present in our subjects as well with a median pH in the normal range NIV which has been clinically used for hypercapnic respiratory failure in CF, but little is known about its physiological effects, particularly in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that a concomitant metabolic alkalosis contributes to hypercapnic respiratory failure in exacerbations of adult CF and that these patients less frequently exhibit acidosis than COPD patients due to the abnormal electrolyte transport in CF patients compared to COPD, even during exacerbations [ 35 , 36 ]. This may have been present in our subjects as well with a median pH in the normal range NIV which has been clinically used for hypercapnic respiratory failure in CF, but little is known about its physiological effects, particularly in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CF are prone to the development of metabolic alkalosis [7-9], which creates a physiologic diminution of respiratory effort that can be detrimental in CF patients , who suffer from chronic lung injury. Metabolic alkalosis could also be the initial presentation or complication of cystic fibrosis in infants and children [10].…”
Section: Introductionmentioning
confidence: 99%
“…8H, I). Nevertheless, the moderate defect may be related to the metabolic alkalosis observed in CF patients [121][122][123][124].…”
Section: Kidneymentioning
confidence: 99%